PENGEMBANGAN DAYA TARIK WISATA KESENIAN SIKAMBANG DI KABUPATEN TAPANULI TENGAH - Intania Sitio; Mimin Sundari Nasution (Universitas Halu Oleo, 2022)
This study uses the tourism development theory by Cooper in Sunaryo 2013, with the indicators, namely institutions, accessibility, amenities, public facilities and tourist attraction objects. This study uses a purposive sampling technique with qualitative research and the necessary data such as primary data and secondary data obtained through observation, interviews, and documentation, then analyzed based on the research problem. The results of this study indicate that tourism development based on predetermined indicators is still not optimal, as evidenced by accessibility and public facilities that do not meet. Then the supporting factors for this tourism development are the existence of institutions or organizations involved in tourism development in Central Tapanuli Regency, tourist objects in Central Tapanuli Regency have local artistic characteristics, and community participation is considered quite high. Meanwhile, the inhibiting factors are limited funds and land ownership status.